2017
DOI: 10.4055/cios.2017.9.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Plate Osteosynthesis Using a Screw Compression Method for Treatment of Humeral Shaft Fractures

Abstract: BackgroundThis study aims to compare the surgical outcomes of open reduction and internal fixation (ORIF) and minimally invasive plate osteosynthesis (MIPO) using a screw compression method in simple humeral shaft fractures.MethodsThis retrospective study was performed with 50 patients who had surgical interventions for the treatment of simple humeral shaft fractures and had follow-ups of at least 12 months in Ulsan University Hospital between August 2008 and June 2015. Group 1 included 23 patients treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…17 studies [ 8 , 14 , 17 , 19 , 24 , 26 , 27 , 30 32 , 34 , 36 , 39 , 43 , 44 , 46 , 48 ] reported on the effect of minimally invasive plate osteosynthesis, consisting of 436 patients. In 12 patients (3%), treatment was complicated by secondary RNP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 studies [ 8 , 14 , 17 , 19 , 24 , 26 , 27 , 30 32 , 34 , 36 , 39 , 43 , 44 , 46 , 48 ] reported on the effect of minimally invasive plate osteosynthesis, consisting of 436 patients. In 12 patients (3%), treatment was complicated by secondary RNP.…”
Section: Resultsmentioning
confidence: 99%
“…In 14 out of 467 patients (3%) in whom an anterolateral approach was used [ 17 19 , 22 , 24 , 26 , 27 , 30 32 , 34 , 36 , 39 , 43 , 44 , 46 , 48 ] and in 17 out of 356 (5%) patients in whom a posterior approach was used [ 8 , 14 , 23 , 25 , 40 , 41 ], treatment was complicated by secondary RNP (Table 6 ). In none of the 46 patients in whom a lateral approach was used secondary RNP occurred [ 16 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MIPO is a new procedure for treating humeral shaft fractures that require close attention to the periosteum, muscles, and nerves. This technique is commonly used for shaft fractures and metaphyseal fractures associated with osteoporosis that can be treated with indirect reduction as anatomical reduction is not required, as well as comminuted fractures that can be treated with bridging plate fixation and achieve good results [12,14]. This technique has the advantage of requiring less soft tissue dissection and avoiding the need to expose the radial nerve, resulting in a lower risk of iatrogenic radial nerve palsies and deep infection [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although open dynamic compression plating (ORIF) provides more accurate anatomical reduction and rigid fixation and reduces the risks of malunions, it requires wide intraoperative exposure with more soft tissue injury. is may contribute to high infection rates and increased rates of nonunion due to violation of soft tissue at the fracture site and severance of periosteal blood supply [7].…”
Section: Introductionmentioning
confidence: 99%